ANALISIS PENGARUH ORIENTASI PASAR DAN STRATEGI BERSAING TERHADAP KINERJA PELAYANAN SECARA SIMULTAN UNTUK MENINGKATKAN KEUNGGULAN BERSAING (Studi Kasus Pada Bengkel Jaya Makmur Motor Di Purwodadi Grobogan) - Prakoso, Muchamad Sigit (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to determine the extent to which a bengkel jaya makmur motor heyday in providing the best quality service to its customers through service performance variables are influenced by variables of market orientation and competitive strategy that will have an impact on competitive advantage. Seeing the number of customer complaints phenomenon that appears to care less than the maximum, then the study was conducted to analyze how to improve the service performance through increased market orientation and competitive strategies that have an impact on competitive advantage to the company.Methods of data collection for this study through questionnaires using purposive sampling method. Respondents for this study are customers who use the services of a bengkel jaya makmur motor in Purwodadi Grobogan who have used the service fees as much as 2 times, totaling 60 people with the criteria of a minimum age of 16 years and maximum 55 years. Data analysis tool used is multiple regression which first tested the validity and reliability, classical assumption, hypothesis testing via t-test, F and coefficient of determination (R2)From the analysis using multiple regression can be seen that the market orientation variable (X1) and competitive strategy (X2) together significantly influence service performance variables (Y1) and subsequent market orientation variables (X1), competitive strategy (X2) and performance services (Y1) jointly significant effect on competitive advantage (Y2). And from this study also found that the variable performance of services (Y2) in mediating the effect of market orientation (X1) with a competitive advantage (Y2) and competitive strategy (X2) with a competitive advantage (Y2).